Boosted photogenerated carriers separation in Z-scheme Cu3P/ZnIn2S4 heterojunction photocatalyst for highly efficient H2 evolution under visible light. (21st May 2020) - Yang, Zhenfei; Shao, Luhua; Wang, Longlu; Xia, Xinnian; Liu, Yutang; Cheng, Shu; Yang, Cong; Li, Sijian
Abstract: Developing low-cost, highly efficient and robust photocatalystic hydrogen evolution system is a promising solution to environmental and energy crisis. Herein, a Z-scheme Cu3 P/ZnIn2 S4 heterojunction photocatalyst was successfully constructed for the first time via a facile solution-phase hybridization method. The optimized Cu3 P/ZIS composite exhibited the highest H2 production rate of 2561.1 μmol g −1  h −1 under visible light irradiation (>420 nm), which was 5.2 times greater than that of bare ZnIn2 S4 and even exceeded the photocatalytic performance of Pt/ZIS composite. The apparent quantum yield of 10 wt% Cu3 P/ZnIn2 S4 can reach 22.3% at 420 nm. The huge boost of photocatalytic hydrogen evolution activity is ascribed to the formation of heterojunction with the built in electric field within Cu3 P/ZnIn2 S4 and Z-scheme charge carriers transfer pathway, which result in efficient separation and migration of charge carriers. In addition, both experimental and theoretical calculation confirmed that the charge-carriers transfer pathway of Cu3 P/ZnIn2 S4 photocatalyst follows the Z-scheme mechanism instead of conventional type-Ⅱ heterojunction mechanism. This work is considered helpful for getting a great deal of insight into constructing high-activity and cost-effective transition metal phosphides (TMPs) based photcatalytic hydrogen production system and rationally designing Z-scheme heterojunction photocatalyst. Graphical abstract: The transfer and separation of photoinduced charge carriers of Cu3 P/ZnIn2 S4 photocatalyst are remarkably enhanced through the Z-scheme transfer route, thus achieving highly efficient photocatalytic hydrogen production. Image 1 Highlights: The direct Z-scheme Cu3 P/ZnIn2 S4 (CPZ) photocatalyst was constructed. CPZ photocatalyst exhibited excellent photocatalytic hydrogen activity. The Z-scheme transfer route resulted in efficient charge separation and migration. It offered a deeper understanding of rationally designing Z-scheme photocatalyst.